Effect of humic acid on soil properties and crop production– A review - BHATT, POOJA; SINGH, V K (The Indian Journal of Agricultural Sciences, 2022)
Many studies have been made in recent years to improve the quality and increase the quantity of agricultural yield. Mechanization and novel hybrid seeds are not the only factors contributing to agricultural advancement and progress; soil quality also plays an important role. It is common for soils that lack organic matter to be unfit for plant growth. Humic compounds have begun to be added to soil in different regions of the world to address this issue and boost agricultural yields. Nowadays, humic acid (HA) is available in different forms (powder, granule, liquid & flakes) in the market and can be applied to crops or soil by various techniques, i.e. soil application, foliar application, seed treatment, root dipping, through drip irrigation and along with inorganic fertilizers but soil application is found most effective in numerous studies. To know the optimum dose of the humic acid, various studies were conducted on crops and discovered a positive response in yield attributed to character, yield, and soil properties. This review enlightens the relevance of humic acid on different crops and soil health, and boosts agricultural productivity.